Strategi Penjurubahasaan Konsekutif Pada Mahasiswa Penjurubahasaan Konsekutif - Jasmine Sjariefah; Sugeng Hariyanto (UPT P2M Politeknik Negeri Malang, 2025)
This study explores the consecutive interpreting strategies employed by a graduate student of Linguistics with a focus on translation at Universitas Brawijaya. Using a descriptive qualitative method, the research analyzes recorded class simulations set in a hospital context. The data, transcribed from role-play exercises involving a doctor, an interpreter, and a patient’s mother, was examined using Faerch and Kasper’s (1983) theory of interlanguage communication strategies, namely reduction strategy and acquisition strategy. The findings identify two main strategy categories: reduction strategies (such as omission and incomplete sentences) and achievement strategies (such as assistance and elaboration). Skipping was found to be the most frequently used strategy, typically involving the exclusion of repetitive or predictable information to ease delivery without distorting the message. However, issues such as unclear articulation and the use of local dialects occasionally hindered effective communication. The study contributes insights into how interpreting strategies are applied in real-time contexts by student interpreters and offers suggestions for enhancing interpreter training programs.